Green procurement practices and performance of star-rated hotels in ghana: The moderating role of guests' green purchasing behaviour - Quaidoo, George (University of Cape Coast, 2024)
The SDGs of sustainability continues to be crucial among researchers as well as firms. Hotels are forced to engage in acts that are considered green as customers now demand more of such practices from their service providers. The current study examined the impact of green procurement practices on the performance of star-rated hotels in Ghana taking into account the moderating role of guests‟ green purchasing behaviour. The study used the green purchasing behaviour theory, and the lodging theory to determining how green procurement practices would make star-rated hotels in Ghana realise effective performance through the impetus of guests‟ green purchasing behaviour. The study utilised the positivist paradigm, causal research design, quantitative research approach, and structured questionnaire. Out of the 348 questionnaires issued, 320 were returned indicating a response rate of 91.95%. The data was processed and analysed with SPSS version 27, and SmartPLS-SEM 4 software. Findings of the study indicated that, the constructs of green procurement practices positively and significantly improve star-rated hotels‟ performance in Ghana. Further, the impact of green procurement practices on star-rated hotels‟ performance in Ghana was also shown to be positively and statistically significant when guests‟ green purchasing behaviour was included. In conclusion, integrating green information systems, supplier collaboration, and supplier environmental certifications represents a strategic approach for star-rated hotels in Ghana to enhance performance while promoting environmental sustainability.
Keywords: Green Procurement Practices; Guests‟ Green Purchasing Behaviour; Hotel Industry; Organisational Performance; Star-Rated Hotels